BAHASA SINGKAT, MAKNA DANGKAL: ANALISIS PENGARUH KOMUNIKASI DIGITAL TERHADAP KETERAMPILAN MENULIS SISWA SEKOLAH DASAR - Suci Marfira; Putri Widya Sari; M.Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital communication has influenced elementary school students’ language use, especially in writing activities. This study aims to analyze the influence of digital communication on students’ writing skills through a Systematic Literature Review (SLR). The study used the PRISMA method with data sources from Google Scholar and Crossref published between 2016–2026. The findings show that digital communication has both positive and negative impacts on writing skills. Negative impacts include the use of slang, abbreviations, and nonstandard language in academic writing. Meanwhile, positive impacts include increased creativity, motivation, and students’ interest in writing through digital media. Therefore, digital communication can become both a challenge and an opportunity in developing elementary school students’ writing skills.